Dynamic Pricing and Consumer Fairness Perceptions - Haws, Kelly L.; Bearden, William O. (Journal of Consumer Research, 2006)
Abstract Dynamic pricing practices by sellers in response to segment and individual-level differences have been made more feasible as internet buyer behavior increases. While benefits from these pricing practices can accrue to sellers and buyers, the potential for (un)fairness perceptions to mitigate these advantages is important. In an effort to investigate these issues, this article reports the results of three studies that examine the effects of seller-, consumer-, time-, and auction-based price differences on perceived price fairness and purchase satisfaction. The findings underscore the potential negative effects associated with price differences from dynamic pricing practices.